MODEL ASUHAN KEBIDANAN BERBASIS TEORI HELEN VARNEY DALAM DETEKSI DINI PREEKLAMPSIA KEHAMILAN DI RSIA CITRA KELUARGA KOTA KEDIRI - Indah Indah Rahmaningtyas (Politeknik Kesehatan Kemenkes Malang, 2018)
Pregnancy is a physiological process, normal and natural, but every pregnancy has the potential to become pathological so that midwives can make promotive and preventive efforts to overcome the occurrence of complications / abnormalities in pregnancy. More complications increase during pregnancy and other complications may already present before the pregnancy begins, but increase during pregnancy. Complications that cause 75% of pregnant women died, among others due to: bleeding (28%), pregnancy hypertension (preeclampsia and eclampsia 27%), abortion (14%), infection (11%), complication of childbirth (8%) ,emboli (3%), and others (9%). Preeclampsia in pregnancy plays a major role in morbidity and maternal mortality and perinatal. The incidence of pregnancy hypertension (preeclampsia and eclampsia) in Indonesia reaches about 27%. RSIA Citra Keluarga Kediri is a hospital that provides maternal and child health services has a pregnancy hypertension rate about 18.8%.This research was conducted to Apply Helen Varney Based Maternity Care Model In Early Detection of Preeclampsia Pregnancy at RSIA Citra Keluarga Kediri in 2017. This research is a study case research. The sample taken were pregnant women who had antenatal examination visit who had preeclampsia pregnancy and did not have pregnancy preeclampsia at the time of the research, then responder was given midwifery care with model of midwifery based on theory of Helen Varney and given counseling early detection of pregnancy preeklampsia.Based on the results of research that has been done on the respondents, it can be concluded that the risk factors of preeclampsia pregnancy is the initial screening or tool that was first used for early detection of preeclampsia before performing other physical examination procedures to establish a diagnosis of the results of early detection. Special physical examinations for early detection of preeclampsia pregnancy include examination of BMI, MAP and ROT performed after screening of anmnese results on risk factors (age, parity and pregnancy history and family). Althought, supporting investigations not an accurate examination, for early detection of preeclampsia, but from the results of research proved respondents with risk factors appeared to have positive (+) and two positive (+ +).